2009
DOI: 10.1080/02656730802713565
|View full text |Cite
|
Sign up to set email alerts
|

Solution to the bioheat equation for hyperthermia with La1−xAgyMnO3-δnanoparticles: The effect of temperature autostabilization

Abstract: This work aimed to analyze the possibility and performance of the temperature controlled hyperthermia based on AC heating of magnetic nanoparticles with low Curie temperature. Temperature dependence of dynamic magnetic susceptibility has been studied experimentally on fine powders of La(0.8)Ag(0.15)MnO(2.95) in the frequency range of 0.5-2.0 MHz. Critical drop of the AC magnetic losses was found in the vicinity of the Curie point, T(C) = 42 degrees C. The obtained data was used in the numerical analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…For example, injection of magnetic fluids and nanoparticles was once thought to be of high efficiency in localized tumor ablation [131][132][133][134]. Nevertheless, Babincov et al introduced subdomain dextran-stabilized magnetite particles to absorb heat in the external RF field [135,136].…”
Section: Unexplored Potential Mechanisms For Future Wbhmentioning
confidence: 98%
“…For example, injection of magnetic fluids and nanoparticles was once thought to be of high efficiency in localized tumor ablation [131][132][133][134]. Nevertheless, Babincov et al introduced subdomain dextran-stabilized magnetite particles to absorb heat in the external RF field [135,136].…”
Section: Unexplored Potential Mechanisms For Future Wbhmentioning
confidence: 98%
“…Because of strong temperature dependence of w 00 , the SAR values are calculated both for the ambient temperature and for the temperatures T max corresponding to the maximum values of w 00 . The results looks rather acceptable for applications, especially for the A samples; the detailed numerical calculations for biomedical objects are published elsewhere [25].…”
Section: Article In Pressmentioning
confidence: 98%
“…1(a)-(c) with the solid curves (the corresponding expressions are not shown for short); details are available in Ref. [25]. Typical transient and steady-state solutions of the heat equation are presented in Figs.…”
Section: Article In Pressmentioning
confidence: 99%
“…Most of available hyperthermia therapy, both systemic and targeted, has been reported as adjunctive therapy to support radiotherapy or chemotherapy [63]. Several reasons of tissue damage are reported as to the limited success of hyperthermia [64][65][66]; a few have been mentioned in this review and shown in Table 1.…”
Section: Energy Deposition To the Tumor By Hyperthermiamentioning
confidence: 99%